Enhancing social studies achievement through make-a-match cooperative learning - Fitri, Rahma; Fitrisia, Azmi (Indonesian Research Journal in Education |IRJE|, 2026)
This classroom action research aimed to improve social studies learning outcomes for Grade VII students at SMPN 1 Batusangkar through the implementation of the Make-a-Match cooperative learning model. The study involved 32 students and was conducted in two cycles, each consisting of planning, action, observation, and reflection stages. Data were collected through observation sheets and achievement tests. The findings revealed a significant improvement in both student participation and academic performance. Classical learning mastery increased from 28% in the pre-action stage to 47% in Cycle I and 84% in Cycle II. The average score also improved from 69 in Cycle I to 78 in Cycle II. The Make-a-Match model fostered active engagement, collaboration, and motivation, contributing to better conceptual understanding. These results indicate that the Make-a-Match strategy is effective in enhancing social studies achievement and classroom interaction at the junior secondary level.